La cultura como función determina las dificultades en lo intercultural (2019)
This paper questions the theoretical background that constitutes the basis of well known instruments frequently used in international business. Some theoretical approaches that aim to facilitate intercultural encounters - represented by the work of Geert Hofstede – are based on a descriptive notion of culture, which is just partially useful in the comprehension of the cultural phenomenon. A debate about the descriptive concept of culture is proposed. Taking into account notions such as individual, identification, and culture, and diverse theoretical points of view, the author shows the limitations of the instruments mentioned in terms of validity and reliability.